Downregulation of AZGP1 by Ikaros and histone deacetylase promotes tumor progression through the PTEN/Akt and CD44s pathways in hepatocellular carcinoma. (30th December 2016) - Tian, Hua; Ge, Chao; Zhao, Fangyu; Zhu, Miaoxin; Zhang, Lin; Huo, Qi; Li, Hong; Chen, Taoyang; Xie, Haiyang; Cui, Ying; Yao, Ming; Li, Jinjun
Summary: Ikaros and HDAC regulate AZGP1 expression in HCC. Downregulation of AZGP1 in the serum of HCC was associated with poor prognosis. AZGP1 inhibited cell migration and metastasis through the regulation of the PTEN/Akt and CD44s pathways. Abstract: Increasing evidence has shown that zinc-alpha2-glycoprotein (AZGP1) is associated with the progression and prognosis of several tumor types. However, little is known regarding the underlying molecular mechanisms of AZGP1 in hepatocellular carcinoma (HCC). In this study, we report that transcription factor Ikaros bound to the AZGP1 promoter and increased its expression in HCC cells. The downregulation of AZGP1 was associated with histone deacetylation in HCC. In addition, the positive feedback regulation via acetylation of histone H4-mediated transactivation of the Ikaros promoter and the Ikaros-mediated transactivation of the acetylation of histone H4 were crucial for regulating AZGP1 expression in HCC cells. Moreover, low serum AZGP1 level in HCC patients was associated with poor prognosis. The ectopic overexpression of AZGP1 or recombinant AZGP1 protein inhibited HCC cell proliferation, migration and invasion in vitro and in vivo, whereas silencing AZGP1 expression resulted in increased cell proliferation, migration and invasion in vitro . In addition, we found that AZGP1 inhibited cell migration and invasion through the regulation of the PTEN/Akt and CD44s pathways. Collectively, our findings revealed the molecular mechanism of AZGP1 expression in HCC, providing new insights into the mechanisms underlying tumor progression.